Design DNA: at the reflective aspects in the level of design / Izzuddinazwan Misri and Amer Shakir Zainol - Misri, Izzuddinazwan; Zainol, Amer Shakir (Faculty of Art and Design, 2021)
Design DNA derives from the idea of DNA concept, commonly known as the chromosome and genetic formation that make most of the organism and, it has its identical profile and criteria. In Design DNA, it contains the attributes that can be referred to the design levels, which contains the visceral, behavioral and reflective. Hence, each level has its details where makes criteria for the desired design are completed. Moreover, these three levels are segregated with discrete aspects of making design. Continuously, each in-level design is expressed in the recognition perspective, and here, the visceral, behavioral, and reflective parts of design DNA are set to be simplified in terminology. Moreover, certain levels like visceral and behavioral aspect formulation for design DNA have been discussed, but no discussion was made in the reflective level. This study focuses on one perspective of the reflective level part and the suggested formulation in purpose for the complete design DNA.